1997
DOI: 10.2307/2960602
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Environmental Gradients: Temporal and Spatial Variability of Soils and Vegetation in the New Jersey Pinelands

Abstract: Summary1 Environmental variability can occur over various spatial scales, ranging from small patches at the scale of individual plants to long gradients over hundreds of metres. 2 In the New Jersey Pinelands, different species in the diverse shrub understorey of pitch pine (Pinus rigida Mill.) forests are patterned at these various scales. 3 Soil moisture, extractable NH 4 -N and N mineralization rate vary in complex ways, with the scale of spatial patterning changing over time and with depth in the soil profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…In nearby areas with similar climate, the maximum E occurs in May (Domingo et al, 1999). The seasonal pattern of variation in y, high in spring and late autumn and characteristically low in summer when plants actively take up soil water, is well known (Henninger et al, 1976;Ehrenfeld et al, 1997;Gehrels et al, 1998).…”
Section: Dynamics Of Water Balance Componentsmentioning
confidence: 99%
“…In nearby areas with similar climate, the maximum E occurs in May (Domingo et al, 1999). The seasonal pattern of variation in y, high in spring and late autumn and characteristically low in summer when plants actively take up soil water, is well known (Henninger et al, 1976;Ehrenfeld et al, 1997;Gehrels et al, 1998).…”
Section: Dynamics Of Water Balance Componentsmentioning
confidence: 99%
“…However, it was not clear whether and how the rate of N mineralization in soil is related to the growing periods of trees above-ground. Most studies suggest that N mineralization was enhanced during the growing season [14,30], which was, in part, attributed to higher temperature coupled with greater soil moisture in the growing season [31,32]. Zhang et al [33] found that 85% of total annual nitrification and 90% of annual N mineralization took place during the growing season.…”
Section: Dynamics Of Inorganic N and N Mineralizationmentioning
confidence: 99%
“…Nitrogen mineralization varies both spatially (Connell et al 1995;González-Prieto et al 1996) and temporally (Aber et al 1993;Ehrenfeld et al 1997). Knowledge of the temporal variations in N mineralization rates in any ecosystem is important because close coupling between N mineralization and plant primary production allows ecosystems to conserve and use N more efficiently.…”
mentioning
confidence: 99%